Overall-Mouth Disinfection by Photodynamic Therapy Using Curcumin - Araujo, Natalia Costa; Fontana, Carla Raquel [UNESP]; Martinez Gerbi, Marleny Elizabeth; Bagnato, Vanderlei Salvador (Mary Ann Liebert, Inc., 2012)
Background data: Photodynamic therapy is a technique that involves the activation of photosensitizers by light in the presence of tissue oxygen, resulting in the production of reactive radicals capable of inducing cell death. Objective: The present study assessed the overall susceptibility of pathogens of salivary flora to photodynamic therapy after sensitization with curcumin and exposure to blue light at 450 nm. Methods: A randomized trial was executed with 13 adult volunteers. Three different groups were analyzed: L-D- (no light, no drug; control group), L-D+ (treated only with the drug; curcumin group) and L+D+ (treated with drug and light; photodynamic therapy group). Non-stimulated saliva samples were collected for bacterial counts at baseline and after the experimental phase, and adverse events experienced were recorded. Serial dilutions were performed, and the resulting samples were cultured on blood agar plates in microaerophilic conditions. The number of colony-forming units was then determined. Results: There was a considerable difference between the two experimental groups with regard to effectiveness of bacterial reduction. In the L-D+ group, the bacterial decline was considerably smaller (9%) than in the L+D+ group, with a 68% decrease in bacteria. A statistically significant reduction in the bacterial population was observed only in the photodynamic therapy group (p < 0.05). Conclusions: Photodynamic therapy was found to be effective in the reduction of salivary microorganisms. No significant reduction was found for the group in which only curcumin was used, proving the absence of dark toxicity of the drug. This work shows that overall disinfection of the mouth can be done with a simple procedure involving photodynamic action.